Analysis of Scrum Implementation in Digital Startup Product Development - Nurindah Tiffani Rachman; Dedy Sushandoyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
One of the renowned methodology to address product development complexity is Agile methodology. Scrum is the tool of Agile methodology which adopts the Agile manifesto through the incremental and iterative way of developing an IT product. It has been widely used for developing a software project in various organizations and has a reputation for effectively managing the process of product development. However, the application of Scrum often adjusted to fit with the organization. The aim of this paper is to understand the implementation and challenges of Scrum through the interview to the Scrum roles. The needs to build a shippable and working product for immediate business testing or user acceptance are reasons that drive the teams to choose Scrum. The methodology used is qualitative research method using an in-depth interview to the scrum roles that involved in IT product development in the digital startup in Indonesia. The result showed that Scrum makes the process of product development more effective, improves coordination between team members and helps the development team to self-independent in doing the task. Therefore, in summarize, Scrum could manage the process of product development well. Keywords: Digital Startup, Agile Method, Product Development, Scrum